Comparative Analysis of Vocational and Technical Education at the Senior Secondary School Level in Nigeria and United Kingdom - Oyelade, A. F.; Ogundele, R. P. (NIU Journal of Social Sciences; Vol 4 No 1 (2018): KIU Journal of Social Sciences, Vol. 4 No. 1, March 2018, 2018)
This paper is a comparative study of vocational and technical education at the Secondary School Level in Nigeria and United Kingdom. Thus it is interested in comparing this type of education in the two countries. The interest is important because vocational and technical education helps in the socio-economic and political development of individuals and the society. Nigeria is a former colony of Britain. Nigeria professes policy of vocational and technical education in its policy on education. United Kingdom also professes policy of vocational and technical education in its policy on education. Yet while Nigeria has less progress in socio-economic and political development, United Kingdom has great socio-economic and political development. Why are Nigeria and Britain not making about the same level of progress in this context? This is why this study is important. The research method used is comparative analysis with emphasis on Historical approach in Comparative Education Studies. Policies, journals, reports, educational magazines and related official educational websites are used for the content analysis in Historical approach. It was found that Nigerian vocational and technical education at the Secondary School Level achieves less than the education in the United Kingdom. This is because the emphasis on the education in the United Kingdom goes up to the end of Senior Secondary School education. Thus it is recommended that Nigeria pursues free secondary education up to the end of senior secondary school level whereby vocational and technical education would be free up to the end of senior secondary school level. Keywords: Comparative Education study, Nigeria, United Kingdom, Historical approach, Vocational and Technical Education.